Gambaran Pengetahuan Remaja Putri tentang Personal Hygiene - Eka Adimayanti; Dewi Siyamti; Hapsari Windayanti (Universitas Ngudi Waluyo, 2022)
Adolescence is a period of transition or transition from childhood to adulthood marked by physical changes. Young women need education about personal hygiene during menstruation because if personal hygiene is not applied properly it can cause infections in the reproductive organs, fungal and bacterial infections. Young women need education about personal hygiene during menstruation because if personal hygiene is not applied properly it can cause infections in the reproductive organs, fungal and bacterial infections. This study aims to describe the knowledge of young women about personal hygiene. The study was conducted on 76 students of class X, majoring in MM, TKJ, TEI SMK NU Ungaran with a sampling technique using accidental sampling. Knowledge assessment of adolescent girls was carried out using a questionnaire about personal hygiene during menstruation. The results showed an increase in students' knowledge about personal hygiene during menstruation after education about personal hygiene during menstruation. ABSTRAK Remaja merupakan masa transisi atau peralihan dari masa anak-anak menjadi dewasa yang ditandai adanya perubahan fisik. Remaja putri membutuhkan edukasi tentang personal hygiene saat haid karena jika personal hygiene tidak diterapkan dengan benar maka dapat menimbulkan infeksi pada organ reproduksi, infeksi jamur dan bakteri. Penelitian ini bertujuan untuk mengetahui gambaran pengetahuan remaja putri tentang personal hygiene. Penelitian dilakukan pada 76 siswi kelas X, jurusan Multi Media (MM), Tehnik Komputer dan Jaringan (TKJ), Tehnik elektronik Industri (TEI) SMK NU Ungaran dengan teknik pengambilan sampel menggunakan accidental sampling. Penilaian pengetahuan remaja putri dilakukan dengan quesioner tentang personal hygiene saat haid. Hasil penelitian menunjukkan adanya peningkatan pengetahuan siswi SMK NU Ungaran tentang personal hygiene saat haid setelah dilakukan edukasi tentang personal hygiene pada saat haid.